Analysis of Mononuclear Phagocytes Disclosed the Establishment Processes of Two Macrophage Subsets in the Adult Murine Kidney - Zhu, Qian; He, Jian; Cao, Yangyang; Liu, Xiaoli; Nie, Wanyun; Han, Fei; Shi, Peng; Shen, Xiao Z. (Frontiers in Immunology, 2022)
The interstitium of kidney involves a variety of components including resident immune cells, in particular mononuclear phagocytes. However, many proposed markers for distinguishing macrophages or dendritic cells are, in fact, shared by the majority of renal mononuclear phagocytes, which impedes the research of kidney diseases. Here, employing a flow cytometry strategy and techniques of fate mapping, imaging and lineage depletion, we were able to demarcate renal monocytes, macrophages and dendritic cells and their subsets in mice. In particular, using this strategy, we found that even in steady state, the renal macrophage pool was continuously replenished by bone marrow-derived monocytes in a stepwise process, i.e., from infiltration of classical monocyte, to development of nonclassical monocyte and eventually to differentiation to macrophages. In mechanism, we demonstrated that the ligation of tissue-anchored CX3CL1 and monocytic CX3CR1 was required for promoting monocyte differentiation to macrophages in the kidney, but CX3CL1-CX3CR1 signaling was dispensable in monocyte infiltrating into the kidney. In addition to the bone marrow-derived macrophages, fate mapping in adult mice revealed another population of renal resident macrophages which were embryo-derived and self-maintaining. Thus, the dissecting strategies developed by us would assist in exploration of the biology of renal mononuclear phagocytes.